Smart Campus Tools - Bart Valks (A+BE: Architecture and the Built Environment)
In recent years, the density on the Dutch university campus has increased substantially due to a continued growth of student populations. Campus managers face the challenge of accommodating the university’s students and employees mainly in the existing buildings, which are used ineffectively and inefficiently. In order to improve the space use on campus, campus managers need better information about space use. Therefore, this PhD dissertation proposes the use of Smart campus tools: a service or product with which information on space use is collected real-time to improve utilization of the current campus on the one hand, and to improve decision‑making about the future campus on the other hand. The main research question is: How can smart campus tools optimally contribute to the match between demand for and supply of space, both on the current campus and on the future campus?